Advances in the Synthesis of 2D MXenes - Wei, Yi; Zhang, Peng; Soomro, Razium A.; Zhu, Qizhen; Xu, Bin (Advanced materials (Weinheim), 2021)
2D transition metal carbides, nitrides, and carbonitrides, also known as MXenes, are versatile materials due to their adjustable structure and rich surface chemistry. The physical and chemical diversity has recognized MXenes as a potential 2D material with a wide spectrum of application domains. Since the discovery of MXenes in 2011, a wide variety of synthetic routes has been proposed with advancement toward large‐scale preparing methods for MXene nanosheets and derivative products. Herein, the critical synthesis aspects and the operating conditions that influence the physical and chemical characteristics of MXenes are discussed in detail. The emerging etching methods including HF etching methods, in situ HF‐forming etching methods, electrochemical etching methods, alkali etching methods, and molten salt etching methods, as well as delamination strategies are discussed. Considering the future developments and practical applications, the large‐scale synthesis routes and the antioxidation strategies of MXenes are also summarized. In summary, a generalized overview of MXenes synthesis protocols with an outlook for the current challenges and promising technologies for large‐scale preparation and stable storage is provided. The recent progress of MXenes synthesis strategies, including etching, intercalation, and delamination, is summarized. The large‐scale preparation methods for MXenes and their derivates, such as flexible membranes and fibers, are discussed. Moreover, the understanding of the oxidation stability of MXenes and stable storage strategies are also addressed.